Investigation of the Selectivity of Carrier Transport Layers in Wide‐Bandgap Perovskite Solar Cells. Issue 7 (3rd May 2021) - Kavadiya, Shalinee; Onno, Arthur; Boyd, Caleb C.; Wang, Xingyi; Cetta, Alexa; McGehee, Michael D.; Holman, Zachary C.
Abstract : Excellent contact passivation and selectivity are prerequisites to realize the full potential of high‐material‐quality perovskite solar cells, first to maximize the internal voltage (or quasi‐Fermi‐level separation) iV within the absorber, then to translate this high internal voltage into a high external voltage V . Experimental quantification of contact passivation and selectivity is, thus, key to improving device performance. Here, open‐circuit measurements of iV oc and V oc, combined with surface photovoltage measurements, are used to systematically quantify the passivation—using iV oc as a metric—and the selectivity—defined as S oc  =  V oc / iV oc —of a range of common carrier transport layers to wide‐bandgap (1.67 eV) perovskite absorbers. The resulting solar cells suffer from large voltage deficits, particularly when NiO x is used as the hole transport layer, even though it provides better passivation than its polymer‐based counterparts (PTAA and PTAA/PFN). This indicates a poor selectivity of NiO x ( S oc  < 0.81 for NiO x ‐based devices), whereas devices using polymer‐based hole transport layers exhibit high selectivity ( S oc  = 0.94–0.95). In agreement with recent reports, this low selectivity is attributed to the formation of an interlayer of non‐perovskite material with high resistance to holes at the perovskite/NiO x interface. These measurements also imply that the selectivity of the C60‐based electron transport layers is relatively good. Abstract : Herein, the passivation and the selectivity of a range of common electron and hole transport layers to wide‐bandgap perovskite solar cells are systematically quantified by comparing their internal voltage iV oc, external voltage V oc, and surface photovoltage SPV. The origins of voltage losses in these devices are explained and what limits the performance of the carrier transport layers is identified.